ANALISA VIDEO YOUTUBE “BUAH MANIS JAGA KEJAYAAN LELUHUR SUKU BADUY” SEBAGAI RESPON PEMBANGUNAN BUDAYA BERKELANJUTAN - Edy Chandra; Ariani Kusumo Wardhani; Lidya Novita; Vanesa Verensian (Lembaga Penelitian dan Pengabdian Kepada Masyarakat Universitas Tarumanagara, 2021)
The Indonesian nation is a nation known for its natural wealth and cultural and ethnic diversity. One of them is the Baduy Tribe who has been known and talked about by the community. With loyalty to customs and the universe. In the end, a stigma emerged in the community, that the Baduy Tribe is a tribe that sells honey. This stigma has emerged as a controversy after President Jokowi wore traditional Baduy clothing at the state event of the Indonesian MPR Session in 2021, which was raised by several netizens on Twitter social media.The controversy over this statement has aroused the response of netizens in mainstream media, so that it becomes an interesting topic to try to glance at virtual anthropological content on YouTube social media which has been produced by various sources of users of YouTube social media accounts. In this study using a virtual ethnographic research method on a YouTube social media channel called ASUMSI with the category